Measuring Financial Performance Using Economic Value Added On Food And Beverage Companies In The Indonesia Stock Exchange (Idx) Index 2020-2022 - Agung Winardi; Putri Amelia Sudriman; Misbah, Misbah; Maghfirah, Maghfirah; Siti Nurhana; Reski Amelia; Linda Razak (CV. AFDIFAL MAJU BERKAH, 2023)
This study aims: To find out, analyze, discuss and explain financial performance appraisal using the Economic Value Added method for food and beverage companies listed on the Indonesia Stock Exchange for the 2020-2022 period. This research uses a quantitative descriptive analysis method. The samples used were six food and beverage companies listed on the Indonesia Stock Exchange. Calculation results of Economic Value Added for food and beverage companies, there are three companies that produce Economic Value Added or (EVA > 0) during 2020 to 2022, it is stated positive, meaning that there has been additional economic value for the company so that financial performance is declared good. used is secondary data obtained from www.idnfinancial.co.id. The data analysis method used in this study is the panel regression model. Data processing uses the SPSS 22 application. From this study, the results show that the Economic Value Adeed Method has a positive effect on the company's financial performance.